The Impact of Climate-Smart Agriculture Technology on Productivity: Does Row Planting Matter? Evidence from Southern Ethiopia - Workineh Ayenew Mossie (The Scientific World Journal)
The impact of climate-friendly agricultural practices on rural household productivity is not well understood, and the available evidence is mainly qualitative. Therefore, this study investigated the impact of the introduction of Climate-Smart Agriculture Practices (CSA, i.e., row planting) on the productivity of improved wheat producers of rural farmer households in Misha Woreda, the southern region of Ethiopia. For this study, we used the data collected from 202 randomly selected wheat producers through a structured questionnaire. The data were analyzed using propensity score matching (PSM) and the generalized Roy model of the semiparametric local instrument variable (LIV) method. The results of the PSM estimation showed that wheat row planting has a positive and significant impact on productivity. The study found that farmers who sowed wheat in a row produced 1368 kg of wheat per hectare compared to the counterfactual scenario. To further validate whether this result is a pure effect of the row planting technique, we performed a covariate balance test that confirmed the insensitivity of the treatment effect estimates to unobserved selection bias. In addition, the Marginal Treatment Effect (MTE) model also showed that the marginal utility of row planting adoption increases the propensity of farmers to adapt climate-smart agriculture technologies. Therefore, by increasing the productivity of farm households, the expansion of technology will significantly contribute to farmers’ resilience to the harmful effects of climate change and welfare.